Appointment Of Catholic Church Bodies As Legal Entities Capable Of Owning Land Rights: Juridical Analysis Based On Hans Kelsen's Theory Of Legal Rights - Suhartoyo Suhartoyo (Politeknik Siber Cerdika Internasional, 2025)
This study analyzes the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/PNJ/KEM-ATR/BPN/VI/2024 concerning the Appointment of Catholic Church Bodies in the Territory of Indonesia as Legal Entities that Can Have Land Ownership Rights. This study aims to determine the implementation of the granting of land ownership rights for Roman Catholic Church bodies in Indonesia based on the applicable appointment. The analysis was carried out using Hans Kelsen's legal rights theory, which emphasizes the importance of law in protecting the rights of citizens and providing legal certainty for each individual. The results of the study indicate that the decision provides legal certainty for Catholic Church bodies to have land ownership rights used for religious and worship purposes. This study also provides suggestions for developing the authority to implement the decision and creating implementation guidelines at the City and Regency Land Office levels.